2020
DOI: 10.1007/s40415-020-00666-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and antioxidative responses associated with drought tolerance of Lasiurus sindicus Henr. endemic to Thar desert, India

Abstract: Sewan (Lasiurus sindicus Henr.) is an endemic fodder grass of low rainfall sandy habitat of hot Indian Thar desert. To understand drought responses and tolerance mechanism in Lasiurus sindicus, seedling growth, root cell viability, changes in enzymatic antioxidants and oxidative injury were assayed at early stage of seedlings in polyethylene glycol (PEG) 6000 (5, 10 and 20%)-induced drought stress. The reduction of seed germination, seedling growth, relative water content and vigor index was found with high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…•− ) to less harmful H 2 O 2 , reducing DNA, protein, and damage to the membrane [78]. The enzyme activity levels in all soybeans increased dramatically in this study.…”
Section: Discussionsupporting
confidence: 49%
“…•− ) to less harmful H 2 O 2 , reducing DNA, protein, and damage to the membrane [78]. The enzyme activity levels in all soybeans increased dramatically in this study.…”
Section: Discussionsupporting
confidence: 49%
“…Antioxidant enzymes have critical importance in the scavenging of (Goswami et al, 2020). Our result showed that, under drought stress, SOD activity was higher in ZD622 and ZS11 than cultivar GY605.…”
Section: Stomatal Limitations Caused Reduction In Photosynthesis Rwc and Fv/fm In B Napus Under Drought Stressmentioning
confidence: 63%
“…Antioxidant enzymes have critical importance in the scavenging of superoxide ions and resistance to lipidperoxidation. The first enzyme in the antioxidant pathway is SOD, which converts highly reactive OH · radical and superoxide (O .− ) to less toxic H 2 O 2 , which reduces damage to DNA, protein, and membrane (Goswami et al, 2020). Our result showed that, under drought stress, SOD activity was higher in ZD622 and ZS11 than cultivar GY605.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, excessive accumulation of ROS damages photosystem II and obstructs D1 protein synthesis. ROS scavenging mechanisms can be orchestrated by antioxidants (enzymatic or nonenzymatic mechanisms) [113,114]. Enhanced enzymatic antioxidative mechanisms were observed with overproduction of some enzymes, for example CAT, POX, SOD and APX, leading to improved oxidative stress tolerance during, e.g., drought.…”
Section: Phytohormonesmentioning
confidence: 99%